A Bittersweet Recipe: Spaces of Utopia and Imagination in "Harry Potter" Meals - Santos, João (Cadernos de Literatura Comparada (teste), 2017)
My purpose with this paper will be to analyze how food contributes for the creation of relationships between Harry Potter characters and how it helps readers to evaluate certain spaces and moments within the series itself. The existence of food helps to determine some of the most important interactions between characters of the saga and can be seen as part of the narrative device that makes the plot evolve (for example, the very first encounter of the main characters). In order to demonstrate this circumstance, I will be focusing on the imaginative properties of Harry Potter meals, particularly in the final book of the saga, and also how they can be used for the characterization of Utopian and Dystopian spaces in certain moments of the story. The moments before and during the reign of Voldemort, the series main antagonist, may not only be analyzed through contrasting adjectivation or positive and negative emotions, but also through the existence and quality of the food that is presented to the characters. Finally, what I wish to emphasize is that food is a strong psychological component that contributes not only for the happiness or bickering between characters, but it also assists the readers in assessing certain situations and in making their reading of the series a more appealing and delicious activity, confirming the words of George Bernard Shaw that “there is no sincerer love than the love of food.”